Monitoring biofortification program performance and potential for impact: Indicators, methods, and learnings from the commercialization of biofortified crops program in six countries across Africa and Asia - Friesen, Valerie M.; Mudyahoto, Bho; Nyangaresi, Annette M.; Gorla, Ishank; Mbuya, Mduduzi NN (Elsevier, 2024)
Background Biofortification of staple crops is a food-based strategy to reduce the high global burden of micronutrient deficiencies. Monitoring program performance is essential to ensure biofortification programs have high potential for impact; however, few indicators and methods for doing so are publicly available.